Pengaruh Inovasi dan Kreativitas Berwirausaha terhadap Keberhasilan Usaha pada Mahasiswa Prodi Pendidikan Ekonomi - sibarani, ika oftavia; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2025)
This research aims to analyze the influence of entrepreneurial innovation and creativity on business success among economic education study program students. Primary and secondary data in this research are in the form of questionnaires obtained from respondents directly, namely students from the Economic Education Study Program, Department of Economics and Accounting, Faculty of Economics, Ganesha University of Education and secondary data in this research from lecturers, administration and other secondary parties. can be used to assist research. The sampling technique in this research used a type of non-probability sampling called saturated sampling, so a sample of 33 students was taken. Data analysis used SPSS version 26 software using descriptive analysis and the regression analysis used was multiple linear regression analysis with the help of the SPSS version 26 for Windows program. The results of the research show that: (1) Innovation has a positive effect on business success, (2) entrepreneurial creativity has a positive effect on business success, and (3) the influence of innovation and entrepreneurial creativity has a positive and significant effect on business success. This can be seen from the results of multiple linear regression with an X1 value of 0.1388 and an X2 value of 0.430. The results of the t test for the innovation variable have a significant value of 0.001, which is less than 0.05, which means that H1 is accepted and the results of the t test for the entrepreneurial creativity variable have a significance value of 0.000, which is less than 0.05, which means that H2 is accepted, as well as the results of the F test. has a significance value of 0.000, which is smaller than 0.05, which means H3 is accepted